Integration of the Marketplace-Based Locality Application, Literacy, and Gamification to Optimize Generation Z’s Role in the Agro-Industrial Sector for Economic Sustainability - Laura, Komang; Padang, Rikky Rundu; Driya, Putu Dhanu (Journal Research of Social Science, Economics, and Management, 2025)
This study aims to determine the level of product acceptance, including perceptions of the LOCALITY application in terms of perceived usefulness, perceived ease of use, and increased knowledge/awareness of technology use and sustainability, as well as the effectiveness of LOCALITY in improving Generation Z's understanding of agroindustry and sustainable economics. This research represents an effort to accommodate agro-industry actors and foster regeneration in the agro sector through the integration of the LOCALITY platform—based on marketplaces, digital literacy, and gamification. This study employs a research and development model, a method used to design and test the effectiveness of a product. The research was conducted at the Faculty of Economics, Universitas Pendidikan Ganesha, using a survey method and sample testing with 75 student respondents, whose effectiveness was then evaluated using a paired sample t-test. The results showed that respondents rated product acceptance levels very highly, including perceptions of LOCALITY, with total averages for each statement above 86.40. Furthermore, respondents' understanding of agroindustry and sustainable economics increased from an average of 69.32 to 92.53. The Sig. (2-tailed) value in the paired sample t-test was 0.000 (< 0.05), indicating a significant difference in outcomes following use of the LOCALITY application.